2010
DOI: 10.3390/w2010101
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Treatment of Concentrated Black Water in a UASB Reactor at a Short HRT

Abstract: This research describes the feasibility of applying a UASB reactor for the treatment of concentrated black (toilet) water at 25 °C. On average 78% of the influent load of COD at an HRT of 8.7 days was removed. Produced methane can be converted to 56 MJ/p/y as electricity and 84 MJ/p/y as heat by combined heat and power (CHP). Minimum reactor volume at full scale was calculated to be 63L per person (for black water containing 16 gCOD/L produced at 5 L/p/d) and this is more than two times smaller than other type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 30 publications
5
101
1
1
Order By: Relevance
“…A study by de Graaff et al [51] showed that applying UASB treatment to concentrated black water from an experimental vacuum toilet system at ambient temperature, with total influent COD as high as 9800 mg/L and stable COD removal efficiencies of over 80%, could be obtained, with methane generation as high as 1.8 m 3 CH 4 /m 3 treated black water. Ideally, source separation and concentration of organic load could make UASB-type treatment more attractive, due to the low reactor volumes needed and high energetic recoveries.…”
Section: Anaerobic Digestion Systemsmentioning
confidence: 99%
“…A study by de Graaff et al [51] showed that applying UASB treatment to concentrated black water from an experimental vacuum toilet system at ambient temperature, with total influent COD as high as 9800 mg/L and stable COD removal efficiencies of over 80%, could be obtained, with methane generation as high as 1.8 m 3 CH 4 /m 3 treated black water. Ideally, source separation and concentration of organic load could make UASB-type treatment more attractive, due to the low reactor volumes needed and high energetic recoveries.…”
Section: Anaerobic Digestion Systemsmentioning
confidence: 99%
“…The higher the organic content, the more biogas. For blackwater stream where the organic concentration is at least 10 times higher than conventional mixed wastewater [128,129], up to 97% of total COD can be removed and 60% converted to CH4 [127,129,130]. The diversion of urine prevents the inhibition of methanogensis from high levels of ammonium and improves the efficiency of digestion and energy recovery.…”
Section: Energy Recoverymentioning
confidence: 99%
“…Other configurations are being investigated to improve the efficiency of the biodegration of the organics, reduce the hydraulic and solid retention time and recover the dissolved methane loss to the effluent in processes such as ananerobic membrane bioreactors [68,129,130], anaerobic fludized bed reactors [68,131,132], upflow anaerobic sludge blankets [129,133,134], and the combination of MFCs and anaerobic membrane bioreactor [135]. In addition, since organics in human feces are mostly metabolized low molecular weight carbons, co-digestion with food waste which contains higher molecular weight carbons can double the biogas production [127,129]. In response to a European Union Directive requiring diversion of 65% of the 1995 levels of organic wastes from landfills, there were 127 operational food waste anaerobic digesters, with a capacity of 4.6 million tons, installed as of 2006 in Europe [127].…”
Section: Energy Recoverymentioning
confidence: 99%
“…The total wet sludge production was calculated using the volume of the UASB reactor (calculations for the reactor volume are presented in the sub-chapter Calculations for reactor dimensions and land area requirement) and the sludge concentration (34 gCOD/L [27]). The sludge production in the SBR was calculated using a sludge yield of 0.12 kgVSS/kgCOD removed and a sludge concentration of 5.5 gVSS/L [9].…”
Section: A1 Calculations For Energy Balancementioning
confidence: 99%